Engaging creativity: Employing assessment feedback strategies to support confidence and creativity in graphic design practice. Issue 1 (1st April 2017) - Visser, Irene; Chandler, Lisa; Grainger, Peter
Creativity is valued in graphic design practice. However, in design education, it is often hindered by assessment processes when students focus on grade outcomes or become attached to a limited set of concepts drawn from pre-existing knowledge. This article presents a case study from an Australian university, drawing on surveys, focus-group discussions and reflections to examine the implications of assessment feedback on creativity in graphic design pedagogy. Curriculum design and assessment strategies that support student confidence in experimentation and creative capacity, as well as the roles of both educators and students, were considered. The study highlights the benefits of face-to-face feedback throughout the assessment process but recognizes the challenges around the practice. It is suggested that, by rethinking how this form of feedback can be effectively incorporated to support graphic design pedagogy, these challenges can be overcome.